ANALISA PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN KARTU THREE (Studi Kasus Mahasiswa STIE Nasional Banjarmasin) - Sri Mulyani; Mifthahul ismi (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2015)
Abstract, The purpose of this research is to examine and analyze the factors that influence consumer behavior in purchasing decisions Three cellular card that cultural factors, social, personal, psychological and Which factors most influence on purchasing decisions on student cards Three Nasional Banjarmasin. The population in this research were students Nasional Banjarmasin as many as 1009 people and samples taken as many as 100 students as respondents who use Three card. The method used in this research is descriptive method of conducting surveys and conduct analysis of consumer behavior on the decision on a student card purchases Three Nasional Banjarmasin. Results of this research is known that from the 4 factors that influence consumer behavior showed 48.67% as a percentage of cultural factors, social factors 43.27%, 43.33% personal factors, 57% psychological factors. of all of these factors just psychological factors are considered positive influence on purchasing decisions Three cards with the percentage amount by 57%. While other factors considered less influential in purchasing decisions Three card because the total number of each factor is less than 50%, which is supposed overall number should exceed 50% for the variables that determine a positive influence on purchasing decisions Three card.